2019
DOI: 10.3390/cancers11111720
|View full text |Cite
|
Sign up to set email alerts
|

The Histone Methyltransferase DOT1L Is a Functional Component of Estrogen Receptor Alpha Signaling in Ovarian Cancer Cells

Abstract: Although a large fraction of high-grade serous epithelial ovarian cancers (OCs) expresses Estrogen Receptor alpha (ERα), anti-estrogen-based therapies are still not widely used against these tumors due to a lack of sufficient evidence. The histone methyltransferase Disruptor of telomeric silencing-1-like (DOT1L), which is a modulator of ERα transcriptional activity in breast cancer, controls chromatin functions involved in tumor initiation and progression and has been proposed as a prognostic OC biomarker. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 51 publications
(66 reference statements)
3
27
0
Order By: Relevance
“…Epigenetic mechanisms have emerged as contributing factors to carcinogenesis. A recent work from our group elucidated the role of the DOT1L (disruptor of telomeric silencing-1-like) gene as a regulator of ERα activity in estrogen-responsive OCs [ 80 ]. DOT1L, a histone methyl transferase, acts as transcriptional regulator through H3K79 mono-, di-, and tri-methylation.…”
Section: The Role Of Estrogen Receptors In Ovarian Cancermentioning
confidence: 99%
“…Epigenetic mechanisms have emerged as contributing factors to carcinogenesis. A recent work from our group elucidated the role of the DOT1L (disruptor of telomeric silencing-1-like) gene as a regulator of ERα activity in estrogen-responsive OCs [ 80 ]. DOT1L, a histone methyl transferase, acts as transcriptional regulator through H3K79 mono-, di-, and tri-methylation.…”
Section: The Role Of Estrogen Receptors In Ovarian Cancermentioning
confidence: 99%
“…Recently, we demonstrated the key role of the previously identified DOT1L (disruptor of telomeric silencing-1-like) ERα partner [86] in hormone-responsive and endocrine-resistant BC cells [87]. DOT1L catalyzes the mono-, di-and trimethylation of Histone H3 on Lysine-79 (K79); it is involved in different biological processes, such as DNA repair, transcriptional elongation and cell cycle progression and its enrollment in cancer progression has been widely demonstrated in different types of cancers, such as in mixed-lineage leukemia (MLL) in which participates in producing MLL fusion proteins, sustaining leukemogenesis processes [104], prostate cancer [105] and ovarian cancer [106]. Our investigation revealed that its silencing or pharmacological inhibition causes a reduced hormone-responsive BC cell proliferation rate and increased cell death both in vitro and in vivo.…”
Section: Interaction Proteomics As Tool For Estrogen Signaling Proteimentioning
confidence: 99%
“…The two original articles both describe studies with ER-coregulators, which control the transcriptional activity of ER [ 1 , 2 ]. A study by Dominic Jones et al [ 1 ] focusses on the role of the histone demethylases KDM3A and KDM4B in breast cancer and this report describes a co-operative mechanism regulating the chromatin transactivation of the ER.…”
mentioning
confidence: 99%
“…As such, their targeting could be a possible therapeutic strategy. The study by Salvati et al [ 2 ] investigated the role of the histone methyltransferase disruptor of telomeric silencing-1-like (DOT1L) in high grade serous ovarian cancer (HGSOC), the predominant form of epithelial ovarian cancer. Having demonstrated that HGSOC cancers with high co-expression of both estrogen receptor alpha (ERα) and DOT1L are associated with poor survival, the investigators used cell line models to investigate functional co-operation between ERα and DOT1L.…”
mentioning
confidence: 99%
See 1 more Smart Citation